2015
DOI: 10.4103/0976-7800.172349
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial ovarian tumors: Clinicopathological correlation and immunohistochemical study

Abstract: Background:Ovarian cancer is the third leading site of cancer among women, trailing behind cervix and breast cancer.Aim:This study was undertaken to analyze the immunohistochemical (IHC) profile of estrogen receptors (ER), progesterone receptors (PR), Ki-67, and p53 in various ovarian epithelial tumors and attempt correlation with clinical and histopathological findings.Materials and Methods:The present study was conducted over a period of 4 years. A technique of manual tissue array was employed for cases subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
(15 reference statements)
2
7
1
Order By: Relevance
“…In our current study, we found that the majority of serous carcinomas of borderline epithelial ovarian cancer were ER and PR positive (93%), whilst 28% or 33% of women with mucinous carcinoma of borderline epithelial ovarian cancer were ER or PR positive. Interestingly, we also found that PR positivity in both subtypes of borderline epithelial ovarian cancer was higher than that in malignant epithelial ovarian cancer which was consistent with previous findings [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our current study, we found that the majority of serous carcinomas of borderline epithelial ovarian cancer were ER and PR positive (93%), whilst 28% or 33% of women with mucinous carcinoma of borderline epithelial ovarian cancer were ER or PR positive. Interestingly, we also found that PR positivity in both subtypes of borderline epithelial ovarian cancer was higher than that in malignant epithelial ovarian cancer which was consistent with previous findings [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although borderline epithelial ovarian cancer (with its two major histologic tumor subtypes, serous carcinoma and mucinous carcinoma) is another subset of epithelial ovarian cancer that has better clinical outcomes, the frequency of ER or PR positivity has not previously been well studied. One previous study showed 75% of cases were ER positive, and 67% of cases were PR positive [ 20 ], however that study did not take into account the further subtypes of borderline epithelial ovarian cancer. In our current study, we found that the majority of serous carcinomas of borderline epithelial ovarian cancer were ER and PR positive (93%), whilst 28% or 33% of women with mucinous carcinoma of borderline epithelial ovarian cancer were ER or PR positive.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, only 6.6% of BOTs were p53-positive in contrast to benign ovarian tumors where positive reaction was not identified 73 . Interestingly, all 5 mucinous borderline tumors and 4 (57%) out of 7 serous borderline tumors expressed p53 in a recent paper from India 72 . In a work from Poland, as many as 90% of OCs and 94% of BOTs showed positive p53 immunoreactivity, and the staining pattern differed significantly between malignant tumors and BOTs 74 .…”
Section: P53 Expression In Botsmentioning
confidence: 91%
“…Some data reported a complete lack of p53 expression in ovarian tumors of low-malignant potential or a low (<5%) immunoreactivity 45 , 63 - 72 . For example, none of 10 BOTs revealed p53 expression pattern by Gursan et al 69 .…”
Section: P53 Expression In Botsmentioning
confidence: 99%
“…To date such studies are limited. A recent study with a relatively small sample size (n = 16) reported higher positivity of ER and lower positivity of PR in epithelial ovarian cancer with metastases 19 . Another study with small sample size (n = 8) also reported higher positivity of ER in metastatic epithelial ovarian cancer 24 .…”
Section: Introductionmentioning
confidence: 91%